Minibrachium, a new subgenus of Rhamphobrachium (Annelida: Onuphidae) from Australia with the description of three new species - Paxton, Hannelore; Budaeva, Nataliya (Zootaxa, 2015)
This study describes a new subgenus of miniature, progenetic Rhamphobrachium species from eastern Australia. Minibrachium, n. subg. is characterised by such paedomorphic features as lack of peristomial cirri and branchiae, possession of only two pairs of modified parapodia with spiny recurved hooks and very early onset of subacicular hooks. Three new species are described, of which at least R. (Minibrachium) nutrix n. sp., the type species (from Lizard Island, Great Barrier Reef), is a fully grown adult, brooding several 16- to 20-chaetiger juveniles in the parental tubes. Rhamphobrachium (M.) talboti n. sp. (from off Sydney) and R. (M.) fractum n. sp. (from Bass Strait), although twice as large as the type species, have only partially developed frontal lips, indicating either incomplete growth or presenting an additional paedomorphic character. We discuss the position of the new subgenus in the Rhamphobrachium complex and present a key to the subgenera of Rhamphobrachium and species of R. (Minibrachium).